A bug's life (Grolier Enterprises New York, 1998)
A Bug's Life by Disney follows the story of a misfit ant named Flik, who teams up with a quirky group of bugs to save his colony from greedy grasshoppers, celebrating themes of bravery, teamwork, and innovation.